Answer:
The answer to the given problem
is x=-11
Step-by-step explanation:
Given problem is ![3x-4+2(x-5)=9x+8-2x](https://tex.z-dn.net/?f=3x-4%2B2%28x-5%29%3D9x%2B8-2x)
To solve the equation:
![3x-4+2(x-5)=9x+8-2x](https://tex.z-dn.net/?f=3x-4%2B2%28x-5%29%3D9x%2B8-2x)
(multiplying the term with factor)
(adding the like terms)
(adding the like terms)
Now taking the terms to one side
(adding the like terms)
![-2x=22](https://tex.z-dn.net/?f=-2x%3D22)
![-x=\frac{22}{2}](https://tex.z-dn.net/?f=-x%3D%5Cfrac%7B22%7D%7B2%7D)
![-x=11](https://tex.z-dn.net/?f=-x%3D11)
x=-11
Therefore x=-11
The answer to the given problem
is x=-11
Answer:
c and d
Step-by-step explanation:
using the two angles in the triangle, 1 and 2, it can be 180- the sum of angles 1 and 2, which is c. using angle 4, it can also be 180 - the equation for angle 4
Parent function = √x
On stretching vertically by factor of 6
New function G(x) = 6√x
<span>We know that OB bisects EC where they intersect would be at point O,
so the two lengths EO and OC must be equal.
2x - 20 = 70 - x
</span>[adding x + 20 to each side]
2x - 20 + x + 20 = 70 - x + x + 20
[simplifying]
<span>3x = 90
</span>[dividing each side by 3]
<span>
x = 30 would be the answer</span>